Assessment of phosphorylation in Toxoplasma glideosome assembly and function. (23rd May 2014) - Jacot, Damien; Frénal, Karine; Marq, Jean‐Baptiste; Sharma, Pushkar; Soldati‐Favre, Dominique
Summary Members of the phylum Apicomplexa possess a highly conserved molecular motor complex anchored in the parasite pellicle and associated with gliding motility, invasion and egress from infected cells. This machinery, called the glideosome, is structured around the acylated gliding‐associated protein GAP45 that recruits the motor complex composed of myosin A and two associated myosin light chains (TgMLC1 and TgELC1). This motor is presumably firmly anchored to the inner membrane complex underneath the plasma membrane via an interaction with two integral membrane proteins, GAP50 and GAP40. To determine if the previously mapped phosphorylation sites on TgGAP45 and TgMLC1 have a direct significance for glideosome assembly and function, a series of phospho‐mimetic and phospho‐null mutants were generated. Neither the overexpression nor the allelic replacement of TgMLC1 with phospho‐mutants impacted on glideosome assembly and parasite motility. TgGAP45 phosphorylation mutants were functionally investigated using a complementation strategy in a TgGAP45 inducible knockout background. The loss of interaction with TgGAP50 by one previously reported GAP45‐mutant appeared to depend only on the presence of a remaining competing wild type copy of TgGAP45. Accordingly, this mutant displayed no phenotype in complementation experiments. Unexpectedly, GAP45 lacking the region encompassing the cluster of twelve phosphorylation sites did not impact on its dual function in motor recruitment and pellicle integrity. Despite the extensive phosphorylation of TgMLC1 and TgGAP45, this post‐translational modification does not appear to be critical for the assembly and function of the glideosome.